THE INFLUENCES OF BRAND IMAGE AND BRAND AWARENESS THROUGH BRAND TRUST ON REPURCHASE BEHAVIOR IN APP-BASED TRANSPORTATION (CASE STUDY OF THE GOJEK APPLICATION) - Bayu Gede Prandali; Olfebri; Sarinah Sihombing (ASIAN PUBLISHER, 2025)
Digital technology currently plays a significant role in daily life. Digital technology will change human attitudes towards new lifestyles which can influence consumer behavior, including the use of transportation. This makes online transportation companies in Indonesia grow rapidly. Transportation services that are different from conventional transportation mean that the rates and services received by consumers are also different. This research implemented quantitative methods. The sample used in this research was 240 GOJEK consumers and the data was processed using SMARTPLS. The SEM–PLS evaluation model is a reflective measurement that is calculated using validity and reliability, where the validity measurement has 2 criteria, including construct validity by assessing convergent validity and discriminant validity. Convergent validity is a combination of indicators that replace one latent variable. Hypothesis 6 has a significant impact and hypothesis 1 has no significant impact. This illustrates the mediating effect of brand trust in influencing the positive indirect influence of brand image on repurchase behavior.